High Rejection-Ratio IGZO Ultraviolet Phototransistor via Additional Solution Processed ZnO Absorption Layer - Ma, Jin Hyun; Jeong, Jun Hyung; Kang, Seong Jae; Park, Min Ho; Ha, Hyoun Ji; Kim, Eojin; You, Seungyun; Kim, Wonsik; Park, Soo hyung; Kang, Seong Jun (John Wiley and Sons Inc., 2024)
The depletion of the ozone layer over the last four decades has increased Earth's exposure to ultraviolet (UV) radiation, posing significant health risks. Indium-Gallium-Zinc-Oxide (IGZO) phototransistors have emerged as promising UV detection candidates, boasting a wide bandgap (>3 eV), low off-current, high on-current, and stability. However, previous efforts to enhance the photoresponse of IGZO phototransistors focused on visible light absorption layers, neglecting UV detection. Here, zinc oxide (ZnO) nanoparticles (NPs) as an absorption layer in IGZO TFTs for UV phototransistors are introduced. IGZO/ZnO TFTs exhibit robust photoresponsivity for UV light below 360 nm, showcasing rejection ratios (Ruv / Rvis) of 20 258, 62 261, 193 649, and 401 582 for wavelengths of 360, 340, 320, and 300 nm, respectively. The combination of IGZO's wide bandgap with ZnO NPs proves effective for detecting UV light below 360 nm, even at low incident light intensities (15 ？W cm？2). Enhanced photoresponse characteristics are confirmed via ultraviolet photoelectron spectroscopy. This research highlights the potential of IGZO materials for UV phototransistors and introduces a novel perspective on the utilization of an additional absorption layer traditionally employed for the conventional extension into the visible light range.